The assessment of bone metabolism in patients treated by using radiotherapy because of the genital malignancy - Góraj, Elwira; Panek, Grzegorz; Kamińska, Janina; Bidziński, Mariusz; Krynicki, Ryszard; Wierzba, Waldemar (Menopause Review/Przegląd Menopauzalny, 2002)
The aim of this study was the assessment of the disturbances in bone mineral density in 49 patients treated because of endometrial or cervical cancer. Besides of the densitometry examinations, before and after radiotherapy the values of osteocalcin and NTx were estimated. On the basis of performed study increase of bone metabolism was observed. The main evidence of this fact was increase of serum NTx levels. Osteocalcin levels, was significantly higher only in women before 50 years old. The changes in activity in bone markers demonstrate of necessity of monitoring the bone metabolism in patients treated by using radiotherapy because of genital malignancy.